2002
DOI: 10.1099/00221287-148-8-2299
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of microbial communities in aerobic–anaerobic sequencing batch reactors fed with different phosphorus/carbon (P/C) ratios

Abstract: Fluorescence in situ hybridization (FISH) was used to analyse the community composition of a sequencing batch reactor (SBR) operating with aerobic-anaerobic cycling and fed acetate as its sole carbon source. Phosphorus was removed from the SBR microbiologically. Marked shifts in the community structure occurred as the phosphorus/carbon (P/C) ratio in the feed was changed. When the P/C ratio was shifted from 1 :10 to 1 :50, FISH analysis showed that the percentage of β-Proteobacteria fell from ca 77 % of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 30 publications
(35 reference statements)
6
60
0
1
Order By: Relevance
“…De Kreuk and van Loosdrecht (2004) showed by semi-quantitative FISH analysis (subjective approximation) that PAO community in GSBR can be almost completely replaced by GAOs when dosage of phosphate is stopped. Similar changes in abundance of Rhodocyclus-related PAOs, but in flocculent sludge, were observed by Kong et al (2002) in a laboratory-scale reactor fed with acetate as a sole carbon source.…”
Section: Resultssupporting
confidence: 51%
“…De Kreuk and van Loosdrecht (2004) showed by semi-quantitative FISH analysis (subjective approximation) that PAO community in GSBR can be almost completely replaced by GAOs when dosage of phosphate is stopped. Similar changes in abundance of Rhodocyclus-related PAOs, but in flocculent sludge, were observed by Kong et al (2002) in a laboratory-scale reactor fed with acetate as a sole carbon source.…”
Section: Resultssupporting
confidence: 51%
“…It is well known that a high COD/P ratio (above 50 mg COD mg -1 P) in wastewater is highly detrimental to EBPR as this promotes the growth of GAOs [4,21,28,29], but the COD must have a sufficient portion of VFAs or readily biodegradable COD to achieve efficient P removal [3,4,21]. The COD/P ratio in the influent in the current study was 35 and resulted in a DOC/P ratio of 12.…”
Section: C/p Ratio In Influentmentioning
confidence: 89%
“…When Kong et al [28] fed a lab-scale SBR with acetate and a C/P ratio of 10 (close to the ratio examined in our research), the sludge was dominated by Betaprotebacteria (77% as revealed by FISH analysis) and P was totally removed from wastewater microbiologically. However, when the C/P ratio was increased to 50:1, the percentage of Betaprotebacteria fell to 38%.…”
Section: C/p Ratio In Influentmentioning
confidence: 99%
See 2 more Smart Citations